Sonochemical Synthesis of Gold Nanoparticles as A Digital Image-Based Colorimetric Probe for Aluminum Ion Detection - Eduwin Saputra; Sri Juari Santosa (Jurnal Kimia Riset, 2026)
Gold nanoparticles functionalized with ethylenediaminetetraacetic acid (EDTA-AuNPs) were successfully synthesized using a sonochemical approach. The synthesis results show a characteristic red color with a SPR peak at 524 nm. The addition of Al³⁺ ions induces a color change in EDTA-AuNPs to blue with a new absorption peak at 700 nm, indicating nanoparticle aggregation. Transmission electron microscopy data confirmed that EDTA-AuNPs particles were dispersed and aggregated after reacting with Al³⁺. Particle size analysis (PSA) confirmed an increase in particle diameter from 27 nm to 161 nm after the addition of Al³⁺. The colorimetric sensor exhibited high selectivity toward Al³⁺ ions. The quantitative analysis was conducted using both UV-Visible spectrophotometry and colorimeter methods. The UV-Visible spectrophotometer method has a detection limit of 0.15 mM, while the colorimeter shows a sensitivity of 0.07 mM. The integration of digital image-based colorimeter methods enables the development of a portable, sensitive, low-cost, and simple platform for on-site detection of Al³⁺ ions.